Modelling the Safe Harvest Limits and Regeneration Rate of Selected Medicinal Plants under Sal Forests of Doon Valley, Uttarakhand, India - Gera, Neeta; Sharma, A. K. (Indian Forester, 2013)
Majority of the world’s human population, especially in developing countries, depends on traditional medicine based on medicinal and aromatic plants (MAPs). Relatively few MAP species are cultivated. The great majority is still provided by collection from the wild. This trend is likely to continue over the long term due to numerous factors. Cultivation is not necessarily the most beneficial production system. Wild collection practices secure valuable income for many rural households, especially in developing countries. However, over-exploitation of MAPs, has been resulting in the loss of habitat and reduction in the regeneration of the MAP species. For these reasons, approaches to wild MAPs collection that balance the needs of local, regional, and international markets with the need for conservation and sustainable use are urgently needed. The present study was undertaken to develop safe harvesting limits for Andrographis paniculata Nees., Evolvulus alsinoides Linn., Phyllanthus urinaria Linn. and Rauvolfia serpentina Benth. occurring naturally in Sal forests of the Doon valley. Negative linear relationship was observed to exist between regeneration rate and harvesting intensity in all the four plant species at all the three sites. Threshold level of harvest adversely affected the regeneration of the above species.